2015
DOI: 10.1002/ppul.23368
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic pneumonias in children: A review of the epidemiology, diagnosis, and treatment

Abstract: Pediatric eosinophilic pneumonias (EPs) are characterized by a significant infiltration of the alveolar spaces and lung interstitium by eosinophils, with conservation of the lung structure. In developed countries, EPs constitute exceptional entities in pediatric care. Clinical symptoms may be transient (Löffler syndrome), acute (<1 month and mostly <7 days), or chronic (>1 month). Diagnosis relies on demonstration of alveolar eosinophilia on bronchoalveolar lavage, whether or not associated with blood eosinoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 76 publications
0
28
0
8
Order By: Relevance
“…In conclusion, our findings suggest that IL-35 negatively regulates airway eosinophilia, at least in part by reducing the production of eosinophil-attracting chemokines CCL11 and CCL24. Given that increased accumulation of eosinophils is known to be pathogenic in various diseases, such as allergic asthma, eosinophilic pneumonias, and eosinophil-associated gastrointestinal disorders (35)(36)(37)(38)(39), IL-35 may provide a new therapeutic tool to reduce tissue recruitment of eosinophils in such diseases. Furthermore, the suppressive effect of IL-35 on stimulus-induced production of chemokines may not be limited to CCL11 and CCL24; it may well extend to other chemokines targeting different types of leukocyte.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our findings suggest that IL-35 negatively regulates airway eosinophilia, at least in part by reducing the production of eosinophil-attracting chemokines CCL11 and CCL24. Given that increased accumulation of eosinophils is known to be pathogenic in various diseases, such as allergic asthma, eosinophilic pneumonias, and eosinophil-associated gastrointestinal disorders (35)(36)(37)(38)(39), IL-35 may provide a new therapeutic tool to reduce tissue recruitment of eosinophils in such diseases. Furthermore, the suppressive effect of IL-35 on stimulus-induced production of chemokines may not be limited to CCL11 and CCL24; it may well extend to other chemokines targeting different types of leukocyte.…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses, the eosinophil count increases. [ 3 , 33 ] In this study, only 20.7% of patients with AEP had eosinophil counts >500 cells/μL and the average among those with initial peripheral blood eosinophilia was 1390 cells/μL.…”
Section: Discussionmentioning
confidence: 65%
“…64 Increased eosinophils could be pathogenic in various diseases, such as eosinophilic pneumonias, allergic asthma, and eosinophil-associated gastrointestinal disorders. 65,66 Recent findings suggest that IL-35 decreases airway eosinophilia by reducing the production of the eosinophil-attracting chemokines CCL11 and CCL24, which demonstrates that IL-35 may provide a new therapeutic strategy to reduce tissue recruitment of eosinophils in such diseases. 67 In addition, studies have shown that the expression of IL-35 is down-regulated in chronic obstructive pulmonary disease, a chronic bronchitis and emphysema characterized by airflow obstruction.…”
Section: Il-35 and Allergic Airway Diseasementioning
confidence: 99%